Effect of vibration frequency on mechanical properties and microstructure of metal inert gas welded dissimilar AA5083 and AA6061 aluminum alloy joints - Saifudin; Nurul Muhayat; Eko Surojo; M. Refai Muslih; Triyono (Results in Engineering)
This study explores how the frequency of vibrations affects the physical, mechanical, and residual stress properties in dissimilar metals welding between AA5083 and AA6061. The vibration-assisted welding process involves the application of vibration frequencies; 0 Hz, 10 Hz, 30 Hz, and 50 Hz. Weld joints were then examined for their microstructure, tensile strength and impact strength. They were also examined using X-ray diffraction to quantify surface residual stress. The findings suggest that welding with a 50 Hz vibration frequency produced weld metal characterized by a fine and consistent equiaxed microstructure. This welded joint exhibited exceptional mechanical property, boasting an ultimate tensile strength (UTS) of 197.87 MPa, an elongation of 15.28 %, and an impact strength of 8.10 J (J). Moreover, this welded joint displayed the lowest surface residual stress within the weld metal, measuring at 110.9 MPa. The application of high-frequency vibrations during aluminum welding promotes a more homogeneous mixing of molten metals between AA5083 and AA6061 in the weld metal. These vibrations also result in increased internal pressure within the molten weld metal, causing dissolved gas bubbles like H2, O2, and N2 to break and release.